Correlation Between Resilience and Academic Achievement of Higher Secondary Scheduled Caste Students - Nandal, Dr. Naveen; Nandal, Nisha; Dr.Milind, (The journal of contemporary issues in business and government, 2021)
The study aims to find out the correlation between resilience and academic achievement of higher secondary scheduled caste students. The sample selected for the Present study consists of 652 higher secondary scheduled caste students studying in government, government-aided and private schools from Rohtak, Hissar and Sonipat districts of Haryana, India, the survey method used in the study in simple random sampling. For measuring, tool used the Resilience Scale in the year 2018 developed by investigator and the percentage of marks scored in their annual examination has been taken for the study. The data consists the background variables gender, major subject, type, nature and locality of the school, father's and mother's education, father's and mother's occupation and monthly income of the family for the calculation. The data collected is analyzed using 't' test and Pearson product moment co-efficient statistical techniques. The finding shows that i) there is significant difference in stability and resilience of higher secondary scheduled caste students with reference due to their gender. ii) there is significant relationship between the dimensions of resilience and gender of higher secondary scheduled caste students and iii) there is no significant positive correlation between resilience and academic achievement of higher secondary scheduled caste students.